2020
DOI: 10.1101/2020.09.30.320317
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Soil microbial diversity impacts plant microbiota more than herbivory

Abstract: Interactions between plants and microbiomes play a key role in ecosystem functioning, and are of broad interest due to their influence on nutrient cycling and plant protection. However, we do not yet have a complete understanding of how plant microbiomes are assembled. Here, for the first time, we show interactions between plant-associated microbial communities that drive their diversity and community composition. We manipulated soil microbial diversity, plant species, and herbivory, and found that soil microb… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 79 publications
(139 reference statements)
2
2
0
Order By: Relevance
“…Herbivory by shoot-feeding insects was previously shown to affect the rhizosphere community, in line with our results (Yang et al, 2011;Lee et al, 2012;Bezemer et al, 2013;Kong et al, 2016;Malacrin o et al, 2020;Zytynska et al, 2020). However, some studies report similar rhizosphere microbiomes between shoot-herbivore-infested and noninfested plants (O'Brien et al, 2018;Malacrin o et al, 2020).…”
Section: Rhizosphere Microbiome Composition Is Differentially Affected By Shoot and Root Herbivorysupporting
confidence: 92%
See 1 more Smart Citation
“…Herbivory by shoot-feeding insects was previously shown to affect the rhizosphere community, in line with our results (Yang et al, 2011;Lee et al, 2012;Bezemer et al, 2013;Kong et al, 2016;Malacrin o et al, 2020;Zytynska et al, 2020). However, some studies report similar rhizosphere microbiomes between shoot-herbivore-infested and noninfested plants (O'Brien et al, 2018;Malacrin o et al, 2020).…”
Section: Rhizosphere Microbiome Composition Is Differentially Affected By Shoot and Root Herbivorysupporting
confidence: 92%
“…Herbivory by shoot-feeding insects was previously shown to affect the rhizosphere community, in line with our results (Yang et al, 2011;Lee et al, 2012;Bezemer et al, 2013;Kong et al, 2016;Malacrin o et al, 2020;Zytynska et al, 2020). However, some studies report similar rhizosphere microbiomes between shoot-herbivore-infested and noninfested plants (O'Brien et al, 2018;Malacrin o et al, 2020). The variation seen in the literature regarding rhizosphere microbiome responses to shoot herbivory could be explained by factors such as plant-and insect-specific responses, or different bulk soil bacterial communities in the starting soil.…”
Section: Rhizosphere Microbiome Composition Is Differentially Affected By Shoot and Root Herbivorysupporting
confidence: 90%
“…P-values were calculated using the two-sided Fischer's exact test (37), while confidence intervals were calculated using the Newcombe-Wilson method (38), and the correction was made using Bonferroni (39). Comparisons of means were done with General Linear Models in Minitab v. 19.…”
Section: Data Processing Bioinformatics Analysis and Statistical Anal...mentioning
confidence: 99%
“…Bacterial community composition in soils also varies depending upon the root activity and the type of crop/tree species that are unique in their rhizosphere activity. A recent study showed that initial soil microbiome diversity, explained the most similar in plant and herbivore associated microbial communities (19). Accordingly, bacterial functioning in rhizosphere niches and bulk soil can influence the overall health of crops, soil fertility (20), and nutrient cycling (21).…”
Section: Introductionmentioning
confidence: 99%